Internalizing Islamic Values in Student Character Building: A Case Study at SMA Negeri 2 Seunagan, Nagan Raya Regency - Hafzan Bustanul Arifin; Muhammad Syarif; Qurrata Akyuni (Yayasan Pendidikan dan Kemanusiaan Hurriah Aceh, 2026)
This study aims to analyze the process, forms of activities, operational strategies, and the impact of internalizing Islamic values on student character formation at SMA Negeri 2 Seunagan, Nagan Raya Regency. This study employed a descriptive-analytical qualitative approach, collecting data through participant observation, in-depth interviews, and documentation studies with the principal, teachers, students, and parents from January to June 2026. Data analysis followed the interactive model of Miles, Huberman, and Saldana. The results showed that the internalization of Islamic values progresses through three stages: value transformation, transaction, and transinternalization. This process is integrated through intra-curricular, co-curricular, and extra-curricular pathways, utilizing five key strategies: exemplary behavior (uswah hasanah), habituation, persuasive advice (mau'izhah), monitoring, and parental partnership. This internalization is proven to have a significant impact on shaping a holistic student character across five key dimensions: increased worship awareness (spiritual), discipline and courtesy (moral), social empathy (social), ethics-based critical thinking (intellectual), and strong independence and work ethic (productive).